The Effectiveness of Think-Pair-Share Model Toward The Listening Comprehension at SMAN 1 Anggana in The Academic Year of 2021/2022 - Clevara, Yayas; Destari, Dina; Noor, Widya Noviana (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
The main concern of the research was the effectiveness of think-pair- share (TPS) model toward the listening comprehension of the eleventh-grade students at SMAN 1 Anggana in the academic year of 2021/2022. The study aimed to find out the data of the students on listening comprehension by using the TPS model to know whether there was effect of teaching model. The research employed an experimental research design administering two groups with pre-test and post-test. The groups were the experimental group and the controlled group. The experimental group was a group that was given treatment by TPS model for the listening comprehension. In contrast, the controlled group was a group that was provided with the conventional model. The data were taken by administering the fifteen multiple-choice comprehension tests to determine the students’ listening comprehension. The subjects were 66 students of the eleventh-grade students of SMAN 1 Anggana in the academic year of 2021/2022. Each group consisted of 33 students. The treatment was given to the subject in the sixth meeting. Finally, the researcher gave the post-test to the two groups and analyzed the score. Then the data were analyzed by using t-test to determine whether there was a significant difference between the TPS model and the conventional model. The result of the research TPS model has a positive advantage on students’ comprehension.